2006
DOI: 10.3133/tm4a7
|View full text |Cite
|
Sign up to set email alerts
|

Kendall-Theil Robust Line (KTRLine--version 1.0)-A Visual Basic Program for Calculating and Graphing Robust Nonparametric Estimates of Linear-Regression Coefficients Between Two Continuous Variables

Abstract: Line (KTRLine-version 1.0)-A visual basic program for calculating and graphing robust nonparametric estimates of linear-regression coefficients between two continuous variables: Techniques and Methods of the U.S. Geological Survey, book 4, chap. A7, 31 p.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(107 citation statements)
references
References 35 publications
2
105
0
Order By: Relevance
“…, 2007; Claessens et al. , 2006; Granato, 2006). The slope was multiplied by the length of time to estimate total change per month during each period.…”
Section: Methodsmentioning
confidence: 99%
“…, 2007; Claessens et al. , 2006; Granato, 2006). The slope was multiplied by the length of time to estimate total change per month during each period.…”
Section: Methodsmentioning
confidence: 99%
“…Both methods provide robust intercept estimates; Nevitt and Tam (1998) showed that the Theil (1950) method was slightly more robust than the Conover (1980) method using simulated datasets, and Helsel and Hirsch (2002) and Granato (2006) recommended using the Conover (1980) method based on its analogy to the ordinary least squares approach. When testing both methods very similar results were obtained, thus for this analysis we simply selected the first method (Eq.…”
Section: Appendix B: Mann-kendall/theil-sen Trend Analysismentioning
confidence: 96%
“…The slope of the Kendall-Theil line is calculated as the median of all possible pairs of slopes between points. The intercept is calculated so that the line will run through the median of the data used (Granato, 2006). The KendallTheil line is not affected by outliers and therefore is a good representation of monotonic trend if it exists.…”
Section: Long-term Trendsmentioning
confidence: 99%